Estudio energético y cambio de lámparas halogenadas por lámparas led en la bodega de productos terminados en la planta Pronaca Puembo para disminuir el consumo energético - Guallimba Catagña, Carlos Manuel (2017)
The objective of the following project is to improve the energy consumption, taking as a starting point the lighting in the company of PRONACA’S FOOD IN PUEMBO, being the study and changing of the luminaries of the finished product warehouse. The Lighting is a medium or essential element for the development of activities beyond the hours of natural light, the company of PRONACA’S FOOD in PUEMBO, having a working day of 24 hours divided in 2 shifts of 12 hours, arises the need to consider the study and change of halogenated luminaries by LED luminaries, to obtain a saving and rational use of electricity in lighting, the research project has a scope in the optimization of resources that are used for the maintenance that takes place every six months. The project is innovative and has a wider scope such as improving all luminaries to the new LED technology, which has achieved a strong impact on saving and other considerable expenses for the base of operations generating cost reduction and the disposal of waste that is sent to environmental managers.